التحليل المكاني لأنماط توزيع المدن في منطقة الباحة باستخدام نظم المعلومات الجغرافية - حسن عبدالله مرعي العمري (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
تهدف الدراسة إلى التحليل المكاني لتوزيع المدن في منطقة الباحة غرب المملكة العربية السعودية، ولتحقيق هذا الهدف اعتمدت الدراسة على المنهجين الوصفي والتحليل المكاني في بيئة نظم المعلومات الجغرافية لتحليل أنماط وانتشار التوزيع المكاني للمدن وسكانها في المنطقة، واستخدمت الدراسة كثافة كيرنل لمعرفة مدى تباين كثافة التوزيع الجغرافي لسكان المدن، والكشف عن الأنماط المكانية التي اتخذها توزيع المدن في المنطقة حسب حجم السكان.وعليه فقد توصلت نتائج الدراسة الى تراجع كثافة سكان المدن من جنوب شرق المنطقة نحو شمالها، واكدت نتائج مقاييس النزعة المركزية والتشتت ان نمط توزيع المدن في المنطقة نمط عشوائي، واتخذ نمط التوزيع المكاني للمدن في المنطقة اتجاه جنوبي غربي شمالي شرقي، كما اظهرت نتائج معاملي الجار الاقرب وتحليل الارتباط الذاتي المكاني لتوزيع المدن في المنطقة بواسطة مؤشر موران، أن مدن منطقة الباحة تتبع نمط عشوائي في توزيعها؛ مما يعني القبول بالفرضية الصفرية، ورفض الفرضية البديلة، كما أكدت نتائج التحليل المكاني الى تباين النفوذ المساحي لمدن منطقة الباحة، وكذلك تباين البعد من المدن وخدماتها.This study aims to analyse spatial distribution patterns of cities in the Al-Baha region, located in western Saudi Arabia. To achieve this, the research adopts both descriptive and spatial analysis methodologies within a Geographic Information Systems (GIS) framework, focusing on the analysis of spatial patterns and the distribution of urban centres and their populations across the region. Kernel Density Estimation (KDE) is employed to assess variations in the geographic density of urban populations and to identify the spatial patterns of city distribution according to population size.The findings indicate a decline in urban population density from the southeastern part of the region toward the north. Central tendency and dispersion measures confirm that the spatial distribution of cities in the region follows a random pattern. Additionally, the spatial distribution of cities exhibits a southwest-to-northeast alignment. As measured by Moran's Index, the results of the nearest neighbor index and spatial autocorrelation analysis further validate the random nature of urban distribution, supporting the null hypothesis and rejecting the alternative hypothesis. The spatial analysis also reveals significant variation in the spatial influence of cities across the region, alongside disparities in the distances between urban centres and their associated services.